Seeing and Being Seen: The Gaze, Surveillance, and Power in Neil Gaiman’s Coraline - Hukum Thapa (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Neil Gaiman’s Coraline (2002) is a major piece of modern children's and young adult literature that addresses the concepts of autonomy, fear and power through the common motifs of vision and observation. The paper focuses on the concept of the gaze and surveillance as mechanisms of control, identity formation and resistance in the novel. Using Foucauldian notions of panopticism, Lacanian psychoanalytical ideas on visual power relations, and feminist thinking on visual power relations, the study explores the use of surveillance and visual domination to control Coraline and the inhabitants of Other World. It also uncovers that Coraline develops psychologically and acquires moral agency as she comes to recognize the practice of observing and the capacity to defy visual means of control. Special focus is placed on the symbolic meanings of button eyes, mirrors and the omnipresent gaze as expressions of objectification, discipline and resistance. The results indicate that the novel is a critique of oppressive systems of power and conveys perception and critical awareness as key tools for self-determination. This paper foregrounds the politics of seeing and being seen and is a part of a wider conversation about surveillance, subjectivity, and visual culture in children's and young adult literature.